2016
DOI: 10.1038/emm.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

The role of autophagy in allergic inflammation: a new target for severe asthma

Abstract: Autophagy has been investigated for its involvement in inflammatory diseases, but its role in asthma has been little studied. This study aimed to explore the possible role of autophagy and its therapeutic potential in severe allergic asthma. BALB/c mice were sensitized with ovalbumin (OVA) on days 0 and 14, followed by primary OVA challenge on days 28–30. The mice received a secondary 1 or 2% OVA challenge on days 44–46. After the final OVA challenge, the mice were assessed for airway responsiveness (AHR), cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 35 publications
(39 reference statements)
8
97
0
3
Order By: Relevance
“…Although autophagy has recently been demonstrated to play an important role on the regulation of inflammation, the role of autophagy in the process of lung inflammation has been controversial [32-34]. A decrease in the autophagosome has been shown to induce inflammatory responses and the rescue of autophagy may be used as a novel anti-inflammatory target [35]. In avian influenza A-infected lung epithelial cells and PM-induced airway inflammation, autophagy activation is required for the production of proinflammatory cytokines [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although autophagy has recently been demonstrated to play an important role on the regulation of inflammation, the role of autophagy in the process of lung inflammation has been controversial [32-34]. A decrease in the autophagosome has been shown to induce inflammatory responses and the rescue of autophagy may be used as a novel anti-inflammatory target [35]. In avian influenza A-infected lung epithelial cells and PM-induced airway inflammation, autophagy activation is required for the production of proinflammatory cytokines [15].…”
Section: Discussionmentioning
confidence: 99%
“…Окрім того, у дітей із бронхіальною астмою значно збільшується екс-пресія гена ATG5 порівняно зі здоровими дітьми [16]. Інгібування автофагії шляхом виключення гена ATG5, у свою чергу, призводить до зменшення гіперреактивності бронхів, зниження рівня інтер-лейкіну-5, еозинофілів, нейтрофілів бронхоаль-веолярного лаважу в дослідженнях на мишах [14]. Таким чином, мінорний генотип ТТ гена ATG5, імовірно, збільшує активність автофагії і спричи-няє зниження ефективності стандартної терапії бронхіальної астми.…”
Section: îáãîâîðåííÿ òà âèñíîâêèunclassified
“…Слід зазначити, що застосування монтелукасту знижує інтенсивність формування автофагосом, а отже, й інтенсивність автофагії [14]. В іншому до-слідженні доведено залежність активності автофагії в хондроцитах від тривалості застосування декса- Êë³í³÷íà ïåä³àòð³ÿ / Clinical Pediatrics метазону: при короткочасному прийомі активність зростає, а в подальшому знижується [15].…”
Section: îáãîâîðåííÿ òà âèñíîâêèunclassified
“…Furthermore, a study by Poon et al revealed the role of ATG5 in adult asthma, and also found an increased number of autophagosomes in fibroblast and epithelial cells from severe asthmatics when compared to healthy volunteers 15 . Recent studies show that there is emerging evidence for the role of autophagy in both eosinophilic 18 and neutrophilic asthma 19 , and convey its link to severe asthma and fibrotic tissue remodeling.…”
Section: Evidence Of Autophagy In Asthmamentioning
confidence: 99%
“…One of the exciting features of this pathway is that it can be inhibited at several steps, including initiation and vesicle elongation, autophagosome formation and maturation, and autophagosome lysosome fusion. Emerging evidence suggests that autophagy inhibition at the very first step is beneficial in an ovalbumin-induced model of asthma in mice, where 3-methyl adenine, a class III PI3K inhibitor, reduced the expression of autophagy marker LC3B with simultaneous reduction in airway eosinophilia 18 . However, there is a need for more research in exploring the role of various PI3K inhibitors in the context of autophagy dependent-airway remodeling, using the most suitable models of asthma and COPD, as modulation of autophagy by the PI3K pathway can be an attractive target for both severe asthma and COPD 4750 .…”
Section: Therapeutic Strategies: Novel Autophagy Modulatorsmentioning
confidence: 99%